In vitro evaluation of porcupine bezoar extracts as anticancer agent on A549 -A preliminary study - Firus Khan, Al'aina Yuhainis; Mohd Nasir, Mohd Hamzah; Jalal, Tara Kamal; Razali, Shakirah; Hassan, Habibah; Abdullah Asuhaimi, Faizah; Abdul Wahab, Ridhwan (Juniper Publishers, 2017)
Porcupine bezoar (PB) was reported to possess medicinal properties in old medical manuscript. However, its potential as anticancer agent on human lung cancer cells (A549) is not yet studied. In present study, porcupine bezoar was tested to observe its ability in inhibiting cell growth of cancer cell (A549) and its cytotoxicity on Normal Human Gingival Fibroblast Cell (HGF-1). A549 cells morphology was observed after treated with bezoars for 72 hours. The ability of bezoars to induce DNA damage and apoptosis was analyzed by staining cells with Hoechst 33428(nucleus) and Rhodamine Phalloidin (f-actin). The A549 IC50 is 13.6±1.58μg/ml A549 growths was inhibited in dose-dependent pattern, but no inhibition found on normal HGF-1 cells. Treated A549 morphology shows sign of apoptosis such as DNA fragmentation, cytoplasm shrunk and vacuolation. The finding in this study suggests PB extracts able to inhibit cell growth, induce DNA damage and apoptosis, further analysis need to be done to verify the mechanism.